Administração pública orientada para o desenvolvimento sustentável : um estudo de caso : os ventos das mudanças no Ceará também geram energia - Lage, Allene Carvalho (2001)
This master's degree dissertation makes a theoretical construction of the sustainable development with base in the dimensions of the sustainability - ecological, economical, social, spatial, cultural, technological and politics - and in the participation of the public administration and of the civil society. As a case study, the dimensions of the sustainability are used as a basis to analyse the Wind Energy Project of Ceará, with the purpose of evaluating the viability of this alternative project, that seeks to contribute for the overcoming of the current problems of provisioning of the Brazilian energy section. The end, this research work establishes a new discernment about public administration and your relation with the civil society, the State and the market in the context of the sustainable development, presenting the bases of a new structure of public administration guided for the sustainable development, in the attempt of adding efforts for the appearance in new ways of public administration that promote the more balanced development and fair of the society in harmony with the environment